ماهية السرقة العلمية - يخلف رفيقة (University Of Eloued جامعة الوادي, 2023)
The topic of scientific theft is considered one of the most important topics in the field of scientific research. It has sparked controversy in the search for the nature and causes of the results of scientific theft on its course and the quality of science in terms of its direct impact on the researcher and knowledge. Therefore, through this study, we are trying to find out what scientific theft is in terms of addressing The concepts of the study and the nature of knowledge, and finally the conclusion of the study and a list of references.
What is scientific theft
مداخلة
Keywords: السرقة العلمية; البحث العلمي; النزاهة العلمية; جودة; plagiarism; scientific research; quality; scientific integrity